Digitalisasi Ekonomi Syariah Penerapan Hukum-Hukum Islam Dalam Jual Beli Online - Safira Dhea Fitriani; Margi Rizki Satriana M; Titin Retnosari; Nur Rohmawati (Universitas Siliwangi, 2021)
Technological developments have penetrated into all fields, including buying and selling. In the past, buying and selling activities required sellers and buyers to meet face to face to reach an agreement, in contrast to the current era where technology is increasingly advanced where sellers and buyers do not have to meet in person but the buying and selling process can still take place. This activity is commonly referred to as buying and selling online, where the process takes advantage of the internet network. In Islam this is something new, but that does not mean that this activity is prohibited, as long as it does not violate Islamic principles. This study tries to identify the implementation of Islamic principles in online buying and selling activities both from the products sold and the transaction process. This study uses qualitative research by taking informants from online business owners in Banyuwangi, Gresik and Kediri by indirect interview. The result of this study was all online business actors did tried applying Islamic sharia in the practice of transaction by social media as Whatsapp, Instagram and Facebook and e-marketplace.Keywords: Buying and selling online, Islamic principles.